2008
DOI: 10.1371/journal.pone.0002802
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Multilocus DNA Barcodes from the Plastid Genome Discriminate Plant Species Equally Well

Abstract: A universal barcode system for land plants would be a valuable resource, with potential utility in fields as diverse as ecology, floristics, law enforcement and industry. However, the application of plant barcoding has been constrained by a lack of consensus regarding the most variable and technically practical DNA region(s). We compared eight candidate plant barcoding regions from the plastome and one from the mitochondrial genome for how well they discriminated the monophyly of 92 species in 32 diverse gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
675
7
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(742 citation statements)
references
References 44 publications
(74 reference statements)
47
675
7
13
Order By: Relevance
“…Others explained amplification failure as a result of poor annealing with standard matK or rbcL primers and highlighted the need to redesign species‐specific primers (Kress & Erickson, 2007; Sass et al. 2007; Fazekas et al., 2008; Lahaye et al., 2008; Casiraghi et al., 2010; Roy et al., 2010). According to Casiraghi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others explained amplification failure as a result of poor annealing with standard matK or rbcL primers and highlighted the need to redesign species‐specific primers (Kress & Erickson, 2007; Sass et al. 2007; Fazekas et al., 2008; Lahaye et al., 2008; Casiraghi et al., 2010; Roy et al., 2010). According to Casiraghi et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, matK and rbcL were able to identify species to the Betus and Salix genus level, but did not allow adequate resolution to distinguish among species belonging to these genera and the rate of amplification was low (only 21% of the Salix samples amplified; Jarvinen et al. 2004; Fazekas et al., 2008; von Crautlein et al., 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The technique can be performed using small parts of the organism, so it overcomes the limitation of morphological classification (Hollingsworth et al 2009). In this technique, non-coding regions of DNA are particularly important, as they tend to have the most variation (Fazekas et al 2008). DNA barcoding technology is being used for various purposes in the tree industry.…”
Section: Resultsmentioning
confidence: 99%
“…Given the limitations, an increasing number of studies showed that plant species identification is unlikely accurate and different combinations have been proposed (Fazekas et al, 2008; Kress and Erickson, …”
Section: Assessment Of the Applicability Of Different Combinationsmentioning
confidence: 99%
“…rbcL is the most commonly sequenced gene by plant systematists for phylogenetic purposes, followed by the trnL-F intergenic spacer, matK, ndhF, and atpB (Shaw et al, 2005;Soltis et al, 2001). Additionally, psbA-trnH, rpoB, rpoC, atpFatpH, psbK-psbI, or a combination of several regions has been selected as candidate regions in the chloroplast (Fazekas et al, 2008;Kress et al, 2005;Ma et al, 2010). In the nuclear genome, most single-copy genes, as well as their introns, have been excluded as barcode candidates because of the lack of universal primers for their amplification.…”
Section: Introductionmentioning
confidence: 99%